EXPLORING THE INFLUENCE OF A HISTORICALLY BLACK COLLEGES AND UNIVERSITY ON THE CREATION OF A DIVERSE CARDIOPULMONARY SCIENCE WORKFORCE: A QUALITATIVE STUDY. - Simmons, Mary; Simmons, Jazmyne; Lopez, Ivette A.; Woods, Kandy (Journal of the National Society of Allied Health)
BACKGROUND There is a need to produce highly competent cardiopulmonary professionals who have social concordance with African American and other minority patients. The purpose of this qualitative study was to evaluate the role of a Historically Black College and University (HBCU) in increasing diversity in the field of cardiopulmonary science. The research questions were: 1) How does an HBCU program retain and produce culturally competent respiratory therapists of color? 2) How can the training at an HBCU enhance patient-provider relationships? METHODS A convenience sample was made up of graduates from the cohorts of 2009-2015 (n=15). Semi-structured interviews were used to elicit feedback from graduates of a cardiopulmonary science program (n=15) at the Florida Agriculture and Mechanical University, an HBCU. Interviews were transcribed verbatim. Transcripts of participant responses were analyzed for meaningful themes. A secondary review of data was conducted to confirm and complete the iteration of themes. RESULTS Participants identified social and economic obstacles and practice mentorship as issues associated with minority student retention and graduation. Participants also identified the role of HBCU faculty, lack of diversity in the health professions, and licensure requirements as factors which influence culturally competent communication and treatment of patients of color. DISCUSSION The participants believed that the cardiopulmonary science program helped to facilitate their successful entry into the field, by preparating them to successfully pass the licensure exam. Most participants expressed a need for respiratory therapists of color, to provide culturally competent services to minority patients, and to help address existing health inequities. CONCLUSION There are positive public health implications for a diversified respiratory therapy workforce. The results of this study highlighted the impact of an HBCU education in order to ensure the successful retention and graduation of minority students.